Neutrophil extracellular traps are associated with poor response to neoadjuvant therapy and poor survival in pediatric osteosarcoma - Baron, Szilvia; Binenbaum, Yoav; Maman, Ronny; Fidel, Victoria; Shusterman, Anna; Vaisman, Dmitry; Sher, Osnat; Manisterski, Michal; Shukrun, Rachel; Rössig, Claudia; Elhasid, Ronit (Frontiers in Oncology, 2025)
PurposeOsteosarcoma (OS), the most common primary bone malignancy in childhood poses a therapeutic challenge despite extensive research. Neutrophil extracellular traps (NETs) play a role in the tumor microenvironment (TME) in a variety of cancers, but their role in OS has not been characterized.Experimental DesignThis retrospective cohort study aimed to investigate immune cell infiltration and NETs formation in patients with OS and its association with chemotherapy response and overall survival using immunofluorescence of paraffin-embedded tissue samples.ResultsAs compared to the non-malignant bone tumor Osteoblastoma, OS samples were characterized by a higher proportion of neutrophils exhibiting NETs. High NETs formation on initial diagnostic biopsies, but not Neutrophil to Lymphocyte ratio, the number of tumor-infiltrating neutrophils, CD3+ T-cells or CD8+ T-cells, was associated with poor response to neoadjuvant chemotherapy. The NETs burden in diagnostic biopsies was also correlated with survival: patients with high NETs burden had a mean overall survival of 53.7 months, as compared with 71.5 months for patients with low NETs. Furthermore, metastatic sites exhibited elevated NETs formation compared to primary tumors, and sera from patients with OS induced NETs release in healthy neutrophils, while sera from healthy controls did not.ConclusionsThese data highlight the potential role of NETs in OS’s TME biology, and suggest that NETs released by tumor infiltrating neutrophils can serve as an independent prognostic factor for poor response to neoadjuvant therapy and overall survival in patients with OS. Such insights may inform the development of tailored treatment approaches in OS.